The impact of e-learning during COVID-19 pandemic on students’ body aches in Palestine - Qais B. Yaseen (Nature Portfolio, 2021)
Abstract Musculoskeletal pain is a major concern in our life due to its negative effects on our ability to perform daily functions. During COVID-19 pandemic, several countries switched their teaching programs into e-learning, where students spend long hour using electronic devices. The use of these devices was associated with several musculoskeletal complains among the students. The aim of this study is to evaluate the different body aches associated with e-learning on university students. The subjects of this study were students from An-Najah University in Palestine. 385 questionnaires were filled using Google forms questionnaire and all the subjects were using e-learning due to COVID-19 pandemic. Our study showed that a large percentage of participants used electronic devices for e-learning during the pandemic. The Duration of these devices use was correlated with duration and degree of pain, and associated with the difficulty in ability to perform several daily activities. Furthermore, most of the students used the sitting position with supine bent forward during the device usage. Thus, the university students that participated in this study had an increase in body aches during the e-learning process, and the aches duration and severity increases if the duration of electronic devices usage increase.